2020
DOI: 10.1021/acs.analchem.0c02200
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Photoluminescent Biosensing Based on Graphene Oxide-Coated Microplates: A Rapid Pathogen Detection Platform

Abstract: Pathogenic bacterial contamination is a major threat to safety, human health, and ecosystems. Herein, we report an advantageous single-step, wash-free, and real-time bacterial detection platform operating with a single antibody. Escherichia coli was detected as a model analyte. This technology is based on graphene oxide-coated microplates (GOMs) and photoluminescent bioprobes (PLBs). On the one hand, using nonradiative energy transfer, GOMs are conceived to deactivate the photoluminescence of those PLBs that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Most optical transducers use enzymes that are immobilized on the sensing element to catalytically convert target biomolecules into products. [178][179] The use of biodegradable electrodes is one of the significant advantages of this optical transducer. An optical biosensor is a portable bioanalytical tool comprising a bio-receptor modified electrode coupled or integrated with an optical transducer element.…”
Section: Optical Biosensormentioning
confidence: 99%
See 1 more Smart Citation
“…Most optical transducers use enzymes that are immobilized on the sensing element to catalytically convert target biomolecules into products. [178][179] The use of biodegradable electrodes is one of the significant advantages of this optical transducer. An optical biosensor is a portable bioanalytical tool comprising a bio-receptor modified electrode coupled or integrated with an optical transducer element.…”
Section: Optical Biosensormentioning
confidence: 99%
“…Recently, various types of optical biosensors have been used in the food industry for the rapid recognition of contaminants, toxins and pathogens. [178][179] These biosensors need an appropriate spectrometer to characterize the spectro- showing the lab-on-chip platform including a motherboard PCB that facilitates data readout, a cartridge PCB hosting the microchip and microfluidic chamber, the microchip including an array of 4096 ISFET sensors and an external thermal controller. Furthermore, a microphotograph showing a 6 × 6 subset of the ISFET array and (d) cross-section illustration of the lab-on-chip platform showing the reaction interface.…”
Section: Optical Biosensormentioning
confidence: 99%
“…[54] One recent investigation, represented in Figure 4(B), by Mariana et al, reported the real-time bacterial biosensing platform based on the photoluminescence quenching property of graphene oxide coated microplates (GOMs). [55] A photoluminescent bioprobe (PLB) such as antibody-conjugated quantum dot was used in such a way that Escherichia coli model bacteria-interacting PLBs preserved their photoluminescence while the non-immunointeracting PLBs lose their photoluminescence. Distance between the PLB-Bacteria conjugate and GOMs, as well as the low affinity of the PLB-bacteria conjugate with GO, contributed to the observed fast and highly sensitive detection limit of ∼ 2 CFU ml À 1 .…”
Section: Graphene-based Biosensorsmentioning
confidence: 99%
“…Several mechanisms have been employed to enhance chemical reactivity of the graphene materials, either by defect engineering (increasing intrinsic defects, especially edge defects) or heteroatom doping (introducing boron, nitrogen, sulfur, etc. into the lattice [53] Copyright 2020, Elsevier Ltd. (B) Real-time bacterial biosensing platform based on GOMs using PLB conjugated quantum dots, Reproduced with permission, [55] Copyright 2020, American Chemical Society. (C) ZnO, Bi-metallic layer associated BaTiO 3 based SPR biosensor representation, with graphene top layer, Reproduced with permission, [57] Copyright 2020, Taylor & Francis Ltd. structure), which have recently been reviewed by Komeily-Nia et al.…”
Section: Graphene-based Catalytic Platformsmentioning
confidence: 99%
See 1 more Smart Citation